Economic hardship from the great recession and long-term changes in depression and quality of life. (20th October 2021) - Bonaccio, M; Costanzo, S; Di Castelnuovo, A; Gialluisi, A; Bracone, F; Persichillo, M; Cerletti, C; Donati, MB; de Gaetano, G; Iacoviello, L
Abstract: Background: Economic downturns may have detrimental effects on mental health. We investigated whether economic hardship resulting from the late 2000s great recession is associated with long-term changes in mental health over 12.8 years of follow up. Methods: We analysed data on 2, 001 participants from the CASSIOPEA Study, a sub-cohort of the larger Moli-sani study (2005-2010, Italy), who were re-examined between 2017-2020 (mean age at baseline 53±9 y; 55% women). Economic hardship possibly experienced since participants' first visit was assessed retrospectively by a questionnaire scoring the following domains: 1) change in employment status; 2) financial hardship and 3) financial hardship for health expenditures. An Economic Hardship Score (EHS) was computed (range 0-14), with highest values indicating higher economic hardship. Mental health was reflected by measurements of depression (Patients' Health Questionnaire; PHQ-2; higher values indicating more depressive symptoms) and mental quality of life assessed by the 36-Item Short Form Health Survey (increased values indicating improved quality of life). In this analysis, the exposure was economic hardship and the outcomes were changes in depression and mental quality of life measured after a 12.8-y period. Multivariable linear regression analysis (95%CI) was used. Results: Mean PHQ-2 and SF36 changes over 12.8 years were -0.08 (±1.28) and 0.47 (±9.90), respectively. In a multivariable-adjusted analysis including duration of follow-up, relevant sociodemographic factors, lifestyles, clinical factors and related life course changes, 1-point increment in EHS was associated with increased depression (β = 0.041; 95%CI 0.022, 0.060) and lower mental quality of life (β=-0.037; 95%CI -0.052, -0.021). Conclusions: Economic hardship resulting from the great recession in late 2000s was associated with a deterioration of mental health, as reflected by increased depression levels and reduced mental quality of life. Key messages: Economic hardship resulting from the recession in late 2000s is associated with a deterioration of mental health. These findings support the notion that economic downturns may have detrimental effects on mental health and support the need for adequate strategies for more vulnerable groups.